A educação das mulheres no Brasil: Nísia Floresta e a experiência do Colégio Augusto (1838-1849) - Lonza, Gabriel Battazza (2019)
This dissertation aims to analyze and reflect on the impact of the work of Nísia Floresta Brasileira Augusta (1810-1885) on the history of female education in Brazil, specifically from the experience of the Augusto College, founded and directed by her. Floresta founded the August College for girls in 1838 in the then capital of the Empire, Rio de Janeiro, and applied an innovative pedagogy for the time, which had as its goal to inaugurate a new way of educating Brazilian women. In the College, some subjects that were taught only in male colleges entered the female curriculum. It is considered the foundation of the August College, for its pedagogical pioneering, a moment of great importance for the history of the feminine education in the country. For this reason, Nísia Floresta is considered as one of the forerunners of feminist ideas in Brazil